(untitled) (Edad Media. Revista de Historia, 2026)
This paper aims to increase our knowledge of the personal and political history of Bernat Guilhèm de Montpellier (b. 1202-1238), maternal uncle of King James I of Aragon. Based on the documentary sources, his family origins, relations, early years and participation in political and military activity from 1220 onwards are studied. During the conquest of the kingdom of Valencia, Bernat Guilhèm was a central figure in the siege of Borriana/Burriana (1233) and the defender of the castle of Puig de Santa Maria (1237), where he obtained a great victory over the Valencian Muslims, which generated a whole legend whose iconographic echoes have reached to our day.